New one-pot synthesis of 4-arylpyrazolo[3,4-b]pyridin-6-ones based on 5-aminopyrazoles and azlactones - Shuvalov, Vladislav Yu.; Vlasova, Ekaterina Yu.; Zheleznova, Tatyana Yu.; Fisyuk, Alexander S. (Beilstein Journal of Organic Chemistry, 2023)
An effective one-pot strategy was developed for the synthesis of 4-arylpyrazolo[3,4-b]pyridin-6-ones from pyrazolo[3,4-b]pyridin-6-ones, obtained by reacting 5-aminopyrazoles with 4-arylidene-2-phenyloxazol-5(4H)-ones (azlactones) under solvent-free conditions, through subsequent elimination of a benzamide molecule in a superbasic medium (t-BuOK/DMSO). The fluorescent properties of the synthesized compounds were studied. 4-Arylpyrazolo[3,4-b]pyridin-6-ones luminesce in the region of 409–440 nm with a quantum yield of 0.09–0.23 when irradiated with UV light.
Keywords: 5-aminopyrazole; azlactone; elimination; fluorescence; one-pot synthesis; pyrazolo[3,4-b]pyridin-6-one